KEPEMIMPINAN BERKARAKTER SEBAGAI PONDASI SEKOLAH BERBUDAYA POSITIF - Atik Luthfia Cahyani; Mujahidah, Qonita; Hendri Marhadi; Mahmud Alpusari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Character-based leadership is the primary foundation for building a positive, ethical, and competitive school culture. Principals serve as role models who instill the values ​​of integrity, responsibility, and empathy in all aspects of education. This study aims to describe the role of character-based leadership in shaping a positive school culture and identify effective implementation strategies in the educational environment. The research method used was a case study at SDN 188 PEKANBARU. The results indicate that character-based leadership can create a harmonious school climate, increase teacher and student motivation, and strengthen cooperation among all school members. Furthermore, principals with strong character can be drivers of change toward inclusive, adaptive schools oriented toward the development of Pancasila student profiles. Thus, character-based leadership can be a strategic foundation for realizing a sustainable, positive school culture.